Probing the Needs of Injecting Technical Communication in English Module in Indonesia Railways Polytechnic: A Students’ Perspectives - Fikria, Ainun; Puspitasari, Armyta; Lestianingsih, Dwi (IJET (Indonesian Journal of English Teaching), 2023)
For employment, industries want recent graduates to have strong technical communication abilities. Therefore, it is important for engineering organizations to have competent technical communicators. As a result, this study looks at how Indonesian polytechnic engineering students assess their own technical communication competency needs in terms of knowledge, abilities, and attitudes toward technical communication in English. A survey on students' perceived needs for technical communication skills received responses from 85 diploma students in various engineering courses at a polytechnic. The study's findings showed that the students' knowledge and abilities about technical communication in English were low intermediate (mean > 3,5 score). In comparison to knowledge and attitudes about technical communication in English, skills in technical communication in English had the lowest mean score. This suggested that the pupils lacked technical English communication abilities. Despite this, the study's findings indicate that students understood the importance of technical communication skills for their future careers. Because need analysis is a continuous process for identifying learning needs, this study has shown that it is worthwhile to review the current needs of the polytechnic engineering students since students' responses could serve as a basis for the improvement of the classroom materials. Finally, this study has recommended that technical communication courses be included to the polytechnic education system since they are crucial for employment in a variety of fields, including engineering.